2014
DOI: 10.1002/j.1681-4835.2014.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Themes of Process Assessment in Rural ICT4D Projects: An Analysis of Assessment Approaches

Abstract: Information and Communication Technologies (ICTs) are often perceived as adequate support tools for development activities. However, their successful employment as development enablers requires strategic implementation. Hence, effectively assessing ICT4D initiatives is imperative. This paper elaborates on a Rural ICT4D Project Process Assessment Framework (RICTP-PAF) that seeks to address an often overlooked but relevant evaluation aspect of ICT4D projects. It proposes that the implementation phase of such pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Lastly, SSM provides a contribution by suggesting that findings from problem analysis and deliberation sessions be communicated to all stakeholder groups in languages that they understand. This is practice highly recommended for ICT4D initiatives (Osah, 2012). In this study, this was demonstrated through communication of analysis findings and deliberation resolves to national government, local government representatives, citizen groups, and civil society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, SSM provides a contribution by suggesting that findings from problem analysis and deliberation sessions be communicated to all stakeholder groups in languages that they understand. This is practice highly recommended for ICT4D initiatives (Osah, 2012). In this study, this was demonstrated through communication of analysis findings and deliberation resolves to national government, local government representatives, citizen groups, and civil society.…”
Section: Discussionmentioning
confidence: 99%
“…The term 'civic tech project' is employed to refer to the use of information tech tools to underpin various aspects of civic practices and public services, particularly civic engagement and civic participation aimed at addressing problems as well as contributing to public governance (Hou, 2018). Where conducted in under-resourced communities, such projects may be viewed as ICT4D projects, as they target public development initiatives through ICT support (Osah, Pade-Khene & Foster, 2014).…”
mentioning
confidence: 99%
“…Impact assessment papers range in scope from a study on the impact of ICT investment on human development across 51 countries (Bankole, Shirazi, & Brown, 2011), to an evaluation of a particular project (van der Vyver & Marais, 2015). Method contributions related to impact assessment or M&E range from a high level critique on how ICT4D projects are evaluated , to the development of a more hands-on process assessment framework (Osah, Pade-Khene, & Foster, 2013). General method or process related contributions include studies on project selection (Plauché, Waal, Grover, & Gumede, 2010), user requirements elicitation (Mamba & Isabirye, 2015), project management (Pade-Khene, Mallinson, & Sewry, 2011), policy evaluation (Krauss, 2013), systems thinking (Turpin & Alexander, 2014) and research philosophy (van Zyl, 2015).…”
Section: Method/impact Assessmentmentioning
confidence: 99%
“…Despite the obvious impact of the delay, a comprehensive evaluation of the process and impact of the ICT for education initiatives is imperative (Osah, Pade‐Khene, & Foster, 2014). With the increasing penetration of ICTs into the society, there is a need for schools to reconsider their technology integration strategy of using accessible alternatives both in and outside of schools (Hinostroza, 2018).…”
Section: Introductionmentioning
confidence: 99%